Album studentów Akademii Zamojskiej (1595-1781), oprać. H. Gmiterek, Archiwum Dziejów Oświaty, t. 11, red. K. Bartnicka, Warszawa 1994 ss. 604. - Żołądź, Dorota (Biuletyn Historii Wychowania, 1995)
Album studentów Akademii Zamojskiej (1595-1781), oprać. H. Gmiterek, Archiwum Dziejów Oświaty, t. 11, red. K. Bartnicka, Warszawa 1994 ss. 604.